Weight faltering and its association with wasting and stunting in Indonesian infants - Rizka Dinari; Vicka Oktaria; Madarina Julia; Margaret Danchin (Universitas Gadjah Mada, 2026)
Purpose: To describe the prevalence of weight faltering, wasting, and stunting in infancy and explore their associations. Methods: This secondary analysis used a 2015-2017 birth-longitudinal cohort study in Yogyakarta, Indonesia. Mean Z-scores for weight-for-age (WAZ), length-for-age (LAZ), and weight-for-length (WLZ) were presented. Weight faltering, wasting, and stunting were assessed. Weight faltering refers to a deceleration in weight that crosses two major percentiles relative to the 2006 WHO Child Growth Standards, evaluated at 0-6 and 6-12 months. Wasting is defined as WLZ<-2 SD, while stunting is LAZ<-2 SD. The association between weight faltering and undernutrition at 6 and 12 months was explored using logistic regression. Results: This study included 294 of 422 participants from the original cohort study. The prevalence of wasting and stunting peaked at 7 months (13%, 6/45) and at 12 months (17%, 25/150), respectively. Weight faltering at 0-6 months (10%, 28/293) was higher than in 6-12 months (4%, 10/250). Bivariate analysis showed that weight faltering at 0-6 months was significantly associated with wasting at 6 months (OR 10.89, 95% CI 3.41-34.80, p-value<0.001) and at 12 months (OR 7.17, 95% CI 1.53-33.49, p-value=0.027), but not with stunting. Conclusion: The prevalence of weight faltering and wasting was higher at 6-7 months of life, whereas stunting was higher at 12 months. Despite showing no significant association with stunting, infants with weight faltering have a higher risk of wasting. Identification of weight faltering is essential to signal the need for further clinical investigation and to enable early intervention to prevent the onset of wasting.